2019
DOI: 10.1111/jpi.12577
|View full text |Cite
|
Sign up to set email alerts
|

Identification of oxidative stress–related Xdh gene as a di(2‐ethylhexyl)phthalate (DEHP) target and the use of melatonin to alleviate the DEHP‐induced impairments in newborn mouse ovaries

Abstract: This study, using an in vitro ovary culture model, investigates the mechanisms through which di(2‐ethylhexyl)phthalate (DEHP) impairs germ cell cyst breakdown and primordial follicle assembly. The results indicate the latter effects exerted by 10 or 100 µmol/L DEHP in cultured newborn ovaries were associated with increased levels of reactive oxygen species (ROS) and apoptosis. Based on a transcriptome analysis, we found the expression of the oxidative stress–related gene Xdh (xanthine dehydrogenase) was signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 53 publications
3
23
0
Order By: Relevance
“…The JNK inhibitor SP600125 (Beyotime, S1876) was prepared in DMSO (10 mg/ml) (Niu et al, 2016). All the reagents were diluted to working concentrations using medium and used as indicated in the literature (Niu et al, 2016;Liu et al, 2019).…”
Section: Ovary Culturementioning
confidence: 99%
“…The JNK inhibitor SP600125 (Beyotime, S1876) was prepared in DMSO (10 mg/ml) (Niu et al, 2016). All the reagents were diluted to working concentrations using medium and used as indicated in the literature (Niu et al, 2016;Liu et al, 2019).…”
Section: Ovary Culturementioning
confidence: 99%
“…By transcriptome sequencing, Liu et al also found a key gene in the in vitro cultured (0-3 dpp) mice ovaries named Xdh, which was related with oxidative stress induced by DEHP. Xdh gene knock down by RNAi could lower the oxidative stress and reduce cell apoptosis (34), which provided the evidence of effects of DEHP on oxidative stress and apoptosis by mRNAs sequencing.…”
Section: Discussionmentioning
confidence: 82%
“…In research of toxicology, the selection of toxicant concentration is the key step of the whole experiment. The concentrations of DEHP used in this study were 10 µM (3.9 µg/ml) and 100 µM (39 µg/ml), which were based on our previously dose response test and the papers published by our research group (33,34). Meanwhile, the maximum concentration used in our study (100 µM, 39 µg/ml) is within the widely accepted concentration range in vitro (35,36).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…With the exception of Figla that was expressed, at variable levels, in all clusters, all other genes such as Lhx8 , Nobox and Sohlh1 encoding transcription factors reported to be typical of follicular oocytes (Wang et al, 2017), appeared restricted to a few clusters (2, 3 and 7) assigned to the early follicle stage. Finally, Gdf9 (encoding a growth factor of the TGF-beta family)(Wang & Roy, 2004), Zp2 and Zp3 (encoding zona pellucida proteins)(Dean, 2002, Zhang et al, 2018), and Xdh (encoding a molybdenum-containing hydroxylase involved in oxidative metabolism of purines)(Dwivedi, Arora et al, 2013, Liu, Li et al, 2019), showed an even more restricted expression limited mainly to cluster 7 corresponding to the late follicular stage.…”
Section: Discussionmentioning
confidence: 99%